Combined finite element: forming limit diagram methodology for the development of automotive body stamped parts. (29th September 2008) - Damoulis, G.L.; Gomes, E.; Batalha, G.F.
This paper describes how Finite Element Method (FEM) can be applied in conjunction with a forming limit diagram (FLD) methodology to lay out industrial sheet metal forming processes. A real part and its numerical model were simulated in accordance to real stamping conditions. The distribution of critical strain and thickness along the critical patches were comprehensively analysed. The FEM-FLD methodology and the experimental data revealed the critical areas of tearing and allowed identifying the modifications that need to be performed in the geometry of the tool in order to ensure the success of the industrial forming process.